Effects of a direct compressible co-processed novel excipient on the brittle fracture tendency of paracetamol tablets - Eraga , Sylvester O.; Obikwu , Frances O.; Iwuagwu , Magnus A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The objective of the study was to investigate the effects of a novel co-processed excipient on ameliorating the brittle fracture tendency of paracetamol tablets. A novel co-processed excipient was prepared using the suspension-agitation methods. The prepared excipient was mixed in varying proportions with paracetamol powder and used to produce three batches of tablets (M1-M3) by direct compression. Maize starch mucilage (10 %w/v) was used to prepare a batch of paracetamol granules (M4) by wet granulation and compressed into tablets. Pre- and post-compression parameters were evaluated for all batches. Brittle fracture indices (BFI) of the tablet formulations were determined and compared. Pre- and post-compression parameters of the batches met official compendial specifications and were comparable in their micromeritic properties, tablet weight uniformity, friability, crushing strengths, disintegration times and dissolution profiles. The brittle fracture indices of the tablets were not directly proportional to their tensile strengths and disintegration times. Tablets prepared with the co-processed novel excipient gave superior BFIs in the rank order of M4 > M1 > M2 > M3. The M3 batch of novel excipient tablets gave comparable tablet properties with those of maize starch mucilage. The tensile strengths and brittle fracture tendencies of the novel excipient tablets may suggest that the excipient can be used as an alternative to maize starch mucilage as binder in paracetamol tablet formulations.